Study of highly sensitive C-reactive protein in type 2 diabetes mellitus and prediction of cardiovascular risk with glycemic status - Doraickannu, T.; Sechassayana, T.; Vithiavathi, S.; Varisali, Momin (International Journal of Advances in Medicine, 2019)
Inflammation plays a vital role in accentuating the formation of atherosclerotic plaque in diabetes mellitus. So, the measurements of inflammatory markers provide a method of assessing cardiovascular risk. Among the inflammatory markers, highly sensitive C-reactive protein (hs-CRP) is used to detect the low-level inflammation when it is within the normal range. Also, hs-CRP measurement may be useful for assessment of the risk of complication in diabetes patients. So, the present study is conducted to measure plasma hs-CRP level in T2DM and to determine adequate glycaemic control reduces hs-CRP level. The objectives of this study were to correlate HbA1c and hs-CRP in T2DM and predict cardiovascular risk with glycaemic status. Methods: Authors took 50 diabetic patients. The investigation includes FBS, PPBS, hs-CRP and HbA1c. hs-CRP is measured by immunoturbidimetry method. The reports were collected and compared with normal reference range. Results: The correlation between hs-CRP levels and HbA1c level after six months show a significant relationship where mean HbA1c values on day 1 and after 6 months were 8.088±1.219 and 7.518±0.693 respectively. The hs-CRP values were 2.508±1.050 on day 1 and 2.15±0.927 after 6 months proving that better glycaemic controls decrease hs-CRP thereby decreasing cardiovascular risk. Conclusions: hs-CRP values are directly related to HbA1c and better glycaemic control reduces risk of CVD.